Fleet utilisation in Sri Jaya bus company / Khadijah Abd. Rahman - Abd. Rahman, Khadijah (1983)
Road passenger transport plays an important role in providing the facilities for conveying people to and from work consistently and without undue delay, to seek recreation and pleasure away from their immediate home surroundings, or for travelling to educational centres and shopping centres. A passenger transport undertaking has to ensure that a most efficient and reliable service is given to the public. At the same time, it must acquire a maximum fleet utilisation to be able to increase productivity with less cost possible. However, the problem in utilising of fleet is not uncommon and solutions should be found to remedy the situation. In this thesis, I would like to analyse the problems of fleet utilisation faced by Sri Jaya Kenderaan Sendirian Berhad and to find solutions which I hope would help Sri Jaya Kenderaan Sendirian Berhad to reduce its problems